The poetics of littérature engagée: Hans Magnus Enzensberger - van den Berg, Cilliers (Acta Academica: Critical views on society, culture and politics, 2010)
Issues related to the socio-political role of literature have always been one of the most important themes in the work of Hans Magnus Enzensberger. His notion of littérature engagée and its actual impact has changed from being optimistic in the earlier texts to being more pessimistic in his later work. This change can be read against the background of certain constants in his oeuvre, especially his view of literature as being nonconformist. This article aims to describe this change by referring to a number of relevant texts. In conclusion the role of “context” as a determining factor for the potential impact of literature is considered.